VALSARTAN IN EVERYDAY CLINICAL PRACTICE IN RUSSIA: ANTIHYPERTENSIVE EFFICACY AND INFLUENCE ON SEXUAL FUNCTION IN PATIENTS WITH ARTERIAL HYPERTENSION - V. I. Podzolkov; V. A. Bulatov; A. V. Vigdorchik (Столичная издательская компания, 2016)
Aim. To study antihypertensive efficacy and safety of valsartan-based therapy (Diovan, Novartis Pharma) as well as patient's compliance and influence of treatment on several aspects of sexual function.Material and methods. 114 doctors from 81 medical institutions of Russia participated in this prospective multicenter observation study. 650 hypertensive patients (average age 53,9±0,4 y.o.) were enrolled. The evaluation of therapy efficacy was based on analysis of systolic (SBP) and diastolic (DBP) blood pressure (BP) changes. Safety and compliance of treatment was also analyzed. The evaluation of sexual function was performed with 5 universal questions selected form the International Index of Erectile Function. These questions could be asked in both men and women. The valsartan dose was 80-320 mg OD. A combination of the valsartan with hydrochlorothiazide (12,5-25 mg/d), amlodipine (5-10 mg/d) or any other antihypertensive was allowed.Results. Significant similar decrease of SBP and DBP was observed in smoking and non-smoking patients (37,5/18,5 and 37,6/15,9 mm Hg respectively, р<0,01 vs baseline). 312 patients (56,9% men, 43,1% women) completed sexual function survey. After 12 weeks of treatment the number of patients without sexual activity and with 1-2 successful sexual attempts in the last 4 weeks significantly decreased from 22 to 16% and from 44 to 30% respectively (р<0,05). Significant increase in the number of patients with 5-6 and 7-10 successful sexual attempts was observed (from 7 to 20% and from 0 to 7% respectively, р<0,05). The treatment resulted in significant increase in the number of patients, who characterized their sexual life satisfaction as "very satisfied" (from 11 to 25%, р<0,01).Conclusion. During the course of effective antihypertensive treatment there was a significant increase in sexual function and general satisfaction with sexual life in patients with arterial hypertension, which could have favorable long-term consequences in increased compliance to the antihypertensive therapy.